Irrigation, health and the environment: A literature review with examples from Sri Lanka - Steele, P.; Konradsen, Flemming; Imbulana, K.A.U.S. (International Irrigation Management Institute, 1997)
This paper attempts to present the linkages between irrigated agriculture, human health, and the environment based on a review of data available from Sri Lanka. Section 2, presents the background by reviewing irrigation development in Sri Lanka. Section 3 presents an outline for selecting the key environmental impacts of irrigation development, and suggests physical and economic indicators to quantify these impacts. Section 4 presents the main data with a short explanation of the main irrigation, health, and environment relationships and a review of their current status in Sri Lanka. Section 5 presents the conclusions.